Design and Performance Analysis of 1.8 GHz Low Noise Amplifier for Wireless Receiver Application - A.A Amin; M. S. Islam; A.A.M. Masud; M. N. H. Khan (Institute of Advanced Engineering and Science, 2017)
In present stereo audio system is a most popular audio system for different purposes. Now a day’s stereo system is commonly used in communication and other purposes. Moreover Normalized Least Mean Square (NLMS) based adaptive filtering is an effective filtering process in case of communication and other applications. However adaptive filtering is an adaptive filter process to cancel out the noise from audio signal successfully. Hence the main objective of this paper is to design a NLMS adaptive filter which cancels out the noise from a noisy wave format stereo audio file. Moreover by varying the order of the adaptive filter (such as 8th, 16th, 32th and 64th), the performance of the NMLS adaptive filtered signal with respect to reference and noisy stereo audio signal are analyzed as well.